Copolymer composition for separator and secondary battery including same

The copolymer-based slurry composition improves the heat resistance and adhesive properties of lithium secondary battery separation films, addressing safety and durability issues in conventional polyolefin films.

JP2025503361APending Publication Date: 2025-02-04HANSOL CHEM
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024513772
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-05
Filing Date
2023-01-16
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

Conventional polyolefin separation films in lithium secondary batteries suffer from high thermal contraction and weak mechanical characteristics, posing safety risks due to potential short circuits and explosions.

Method used

A slurry composition is developed using a copolymer composition comprising acrylate-based monomers, vinyl amide monomers, and vinyl pyrrolidone monomers, along with crosslinking agents, which is applied to a porous substrate film to create a separation film with improved heat resistance and adhesive properties.

Benefits of technology

The new separation film exhibits enhanced heat resistance and adhesive strength, ensuring better safety and longevity of lithium secondary batteries by reducing thermal contraction and preventing short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503361000001
    Figure 2025503361000001
  • Figure 2025503361000002
    Figure 2025503361000002
  • Figure 2025503361000003
    Figure 2025503361000003
Patent Text Reader

Abstract

The present invention relates to a copolymer composition including a copolymer containing one or more monomer units selected from the group consisting of 30% by weight to 80% by weight of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units, and 20% by weight to 70% by weight of vinylpyrrolidone monomer units, based on 100% by weight of the total copolymer weight, and a crosslinker, and a slurry composition, a separator, and a secondary battery containing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolymer composition, a slurry composition containing the same, a separator, and a secondary battery. [Background technology]

[0002] Due to their high energy density, lithium secondary batteries are widely used in the electrical, electronic, communications and computer industries. Following small lithium secondary batteries for portable electromagnetic devices, their application areas are expanding to include high-capacity secondary batteries for hybrid and electric vehicles.

[0003] Lithium-ion secondary batteries are insulated by a separator. However, internal or external abnormal phenomena or impacts on the battery can cause a short circuit between the positive and negative electrodes, which can lead to heat generation and explosion. Therefore, it is very important to ensure the thermal and chemical safety of the separator.

[0004] Currently, polyolefin films are widely used as separators, but polyolefins have the disadvantages of severe thermal shrinkage at high temperatures and fragile mechanical properties.

[0005] In order to improve the safety of such polyolefin-based separators, porous separators have been developed in which a mixture of inorganic particles and a binder is coated on a polyolefin porous substrate film.

[0006] That is, in order to suppress thermal shrinkage of polyolefin-based separators due to high temperatures and instability of batteries due to dendrites, inorganic particles are coated on the cross section or both sides of a porous separator substrate together with a binder, whereby the inorganic particles suppress the shrinkage rate of the substrate and the coating layer produces a safer separator.

[0007] To ensure excellent battery characteristics, the coating layer must be uniformly applied and must have strong adhesion to the substrate.

[0008] Furthermore, in order to meet the recent trend towards higher capacity and higher output, it is necessary to further improve the heat resistance of conventional separation membranes. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent No. 10-1430975 [Patent Document 2] Korean Patent Publication No. 10-2006-0072065 Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, the present invention aims to provide a slurry composition having excellent heat resistance and adhesiveness by using a copolymer composition.

[0011] The present invention also provides a separator having excellent heat resistance to which the slurry composition is applied, and a battery having excellent performance using the separator. In particular, the separator has excellent heat resistance when impregnated with an electrolyte.

[0012] As a result, a battery with excellent life characteristics and safety can be realized.

[0013] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0014] According to one aspect of the present invention, there is provided a copolymer comprising at least one monomer unit selected from the group consisting of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units in an amount of 30% by weight or more and 80% by weight or less, based on 100% by weight of the total copolymer weight, and at least one monomer unit selected from the group consisting of vinylpyrrolidone monomer units in an amount of 20% by weight or more and 70% by weight or less, A cross-linking agent, A copolymer composition is provided.

[0015] Another aspect of the present application is a method for producing a polymerizable composition comprising the copolymer composition and and inorganic particles, A slurry composition is provided.

[0016] Yet another aspect of the present application includes the slurry composition, A separation membrane is provided.

[0017] Another aspect of the present application includes the separation membrane, A secondary battery is provided. Effect of the Invention

[0018] The copolymer composition of the present invention can improve the adhesive strength and heat resistance of the slurry composition, increase the adhesive strength with the polyolefin film that is the separation membrane substrate, and improve the heat resistance of the separation membrane (particularly, the heat resistance when impregnated with an electrolyte).

[0019] In addition, a battery having excellent life characteristics and safety can be realized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention. However, these examples are presented only as examples of the present invention and do not define the scope of the invention.

[0021] Prior to this, the terms and words used in this specification and the claims should not be interpreted in a limited manner based on their ordinary or dictionary meaning, but should be interpreted in a meaning and concept that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to explain his / her invention in the best possible manner.

[0022] Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can replace them at the time of this application.

[0023] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. In this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof. In this specification, when a numerical range is indicated as "a to b" or "a~b," "to" and "~" are defined as ≧a and ≦b.

[0024] The copolymer composition according to one aspect of the present application may include a copolymer including one or more monomer units selected from the group consisting of 30% by weight or more and 80% by weight or less of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units, and 20% by weight or more and 70% by weight or less of vinylpyrrolidone monomer units, based on 100% by weight of the total copolymer weight, and a crosslinking agent.

[0025] For example, based on 100% by weight of the total copolymer weight, the content of one or more monomer units selected from the group consisting of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units may be 50% by weight or more and 80% by weight or less, and the content of the vinylpyrrolidone monomer unit may be 20% by weight or more and 50% by weight or less.

[0026] The crosslinking agent introduces a chemically and physically crosslinked structure into the copolymer, and when the copolymer composition is applied to a separator for a secondary battery, the crosslinking agent can improve the heat resistance of the separator and improve the life characteristics and safety of the secondary battery using the separator.

[0027] In particular, since the vinylpyrrolidone monomer unit of the copolymer has a property of being dissolved in an electrolyte, the dissolution of the vinylpyrrolidone can be reduced through a chemical or physical crosslinking structure formed by the crosslinking agent, thereby improving the heat resistance of the separator when impregnated with an electrolyte.

[0028] The chemical crosslinked structure formed by the crosslinking agent is a crosslinked structure formed by a covalent bond, and the physical crosslinked structure formed by the crosslinking agent is a crosslinked structure formed by a bond such as a hydrogen bond or an ionic bond that is not a covalent bond.

[0029] On the other hand, if the content of one or more monomer units selected from the group consisting of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units exceeds the range of the present application, and the content of the vinylpyrrolidone monomer units is below the range of the present application, the heat resistance of the separator to which the copolymer composition is applied may be reduced.

[0030] In addition, if the content of one or more monomer units selected from the group consisting of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units is below the range of the present application and the content of the vinylpyrrolidone monomer units is above the range of the present application, the adhesive strength of the copolymer composition may decrease.

[0031] The acrylate monomer unit may be formed by polymerizing a water-soluble acrylate monomer.

[0032] The vinylamide monomer unit may be formed by polymerizing a water-soluble vinylamide monomer.

[0033] In one embodiment, the acrylate-based monomer unit is formed by polymerizing acrylic acid, methacrylic acid, hydroxylethyl acrylate, hydroxylethyl methacrylate, glycidyl acrylate, glycidyl methacrylate, or a combination thereof, the acrylonitrile-based monomer unit is formed by polymerizing acrylonitrile, methacrylonitrile, or a combination thereof, and the vinylamide-based water-soluble monomer unit is formed by polymerizing vinyl acetamide, methyl ... The acrylamide-based monomer unit may be formed by polymerizing acrylamide, methacrylamide, N-methylmethacrylamide, hydroxyethyl acrylamide, hydroxyethyl methacrylamide, dimethylacrylamide, or a combination thereof, and the vinylpyrrolidone monomer unit may be formed by polymerizing vinylpyrrolidone.

[0034] That is, the copolymer may be formed by copolymerizing at least one monomer selected from an acrylate-based monomer, an acrylonitrile-based monomer, a vinylamide-based monomer, and an acrylamide-based monomer, and a vinylpyrrolidone monomer.

[0035] In an embodiment, the copolymer may include a repeating monomer structure represented by the following Formula 1:

[0036] [ka]

[0037] In the above Chemical Formula 1, R1 to R5 are each independently hydrogen or a linear or branched hydrocarbon having 1 to 4 carbon atoms, X1 and X2 are each independently hydrogen or a linear or branched hydrocarbon having 1 to 20 carbon atoms, X3 is hydrogen, a linear or branched hydrocarbon having 1 to 20 carbon atoms or an acid, X4 is a linear or branched hydrocarbon having 1 to 20 carbon atoms or an alcohol, and a, b, c, d, e and f may be a+b+c+d+e+f=1.

[0038] In the above formula 1, a, b, c, d, e, and f correspond to the weight fraction of each monomer unit, and the sum of the weight fractions of each monomer unit is 1.

[0039] On the other hand, a may be between 0.2 and 0.7, and b+c+d+e+f may be between 0.3 and 0.8.

[0040] Also, b, c, d, e and f may each be 0 to 0.8, provided that any one or more of b, c, d, e and f may not be 0.

[0041] For example, R1 to R4 and X1 to X4 in Formula 1 may each independently include at least one selected from the group consisting of hydrogen, methyl, and ethyl.

[0042] In one embodiment, the crosslinker may include at least one selected from the group consisting of a first crosslinker and a second crosslinker, the first crosslinker may include a double bond, and the second crosslinker may be a compound represented by Formula 2:

[0043] [ka]

[0044] In the above Chemical Formula 2, R6 through R8 may each independently be hydrogen, a linear or branched hydrocarbon having 1 to 6 carbon atoms, an alcohol having 1 to 6 carbon atoms, an acid having 1 to 6 carbon atoms, or a combination thereof.

[0045] For example, the alcohol having 1 to 6 carbon atoms may be -(CH2)2OH, -(CH2)3OH, -(CH2)4OH, -(CH2)5OH or -(CH2)6OH, and the acid having 1 to 6 carbon atoms may be -(CH2)2COOH.

[0046] That is, the first crosslinking agent can introduce a chemical crosslinked structure formed by a covalent bond into the copolymer, and the second crosslinking agent can introduce a physical crosslinked structure formed by a non-covalent bond into the copolymer.

[0047] The first crosslinking agent contributes to improving the heat resistance of a separator to which the copolymer composition of the present application is applied, and the second crosslinking agent contributes to improving the adhesive strength of the copolymer composition of the present application and the heat resistance (particularly, heat resistance when impregnated with an electrolyte) of a separator to which the copolymer composition of the present application is applied.

[0048] In an embodiment, the first crosslinker may be a difunctional or higher functional acrylic monomer or a difunctional or higher functional amide monomer.

[0049] In addition, the first crosslinking agent may be polyethylene glycol diacrylate, N,N'-methylenebisacrylamide, divinyl adipate, 1,4-butanediol divinyl ether, 1,4-cyclohexanedimethanol divinyl ether, 1,6-divinylperfluorohexane, 1H,1H,6H,6H-perfluoro-1,6-hexanediol diacrylate, or a combination thereof.

[0050] In one embodiment, based on 100 parts by weight of the copolymer, the content of the first crosslinking agent may be 0.05 to 5 parts by weight, and the content of the second crosslinking agent may be 0.05 to 5 parts by weight.

[0051] If the content of the first crosslinking agent and / or the second crosslinking agent is below the range of the present application, the heat resistance of the separator to which the copolymer composition of the present application is applied may decrease. In an embodiment, the copolymer may be a random or block copolymer depending on the synthesis process.

[0052] In an embodiment, the copolymer may have a number average molecular weight of 5,000 to 1,000,000.

[0053] If the number average molecular weight of the copolymer is less than 5,000, the fluidity of the copolymer may increase, which may reduce the dispersibility and the heat resistance of the separator.If the number average molecular weight is more than 1,000,000, the viscosity may be too high for practical use, which may clog the pores of the separator, reducing the air permeability and resistance.

[0054] A slurry composition according to another aspect of the present application may include the copolymer composition of the present application and inorganic particles.

[0055] The inorganic particles can be any insulating particles without any limitation, and may be high dielectric constant insulating particles.

[0056] Specific examples of the inorganic particles include Al2O3, AlOOH, SiO2, TiO2, ZrO2, ZnO, NiO, CaO, SnO2, Y2O3, MgO, BaTiO3, CaTiO3, SrTiO3, SiC, Li3PO4, Pb(Zr,Ti)O3 (PZT), (Pb,La)(Zr,Ti)O3 (PLZT), and mixtures thereof.

[0057] The size of the inorganic particles is not particularly limited, and may be, for example, an average particle size of 0.01 μm to 30 μm, more preferably 0.1 μm to 10 μm. If the average particle size of the inorganic particles is less than the preferred range, dispersibility may be reduced, and if it exceeds the preferred range, the thickness of the coating layer after coating may increase, resulting in reduced mechanical properties.

[0058] The shape of the inorganic particles is not particularly limited, and may be, for example, spherical, elliptical, or irregular.

[0059] A separation membrane according to another aspect of the present application may include the slurry composition of the present application.

[0060] The separator may have a heat shrinkage rate of 6% or less in MD (machine direction, longitudinal direction) and TD (transverse direction, width direction) when left at 150° C. for 1 hour.

[0061] The separator may also have a thermal shrinkage rate of 7% or less in the MD and TD directions when immersed in an electrolyte for 12 hours and then left at 150° C. for 1 hour.

[0062] The slurry composition may be coated on at least one surface of a porous substrate film, or the slurry composition may be prepared in the form of a film and attached to a porous substrate film to prepare a separator.

[0063] Meanwhile, the separator can be used as a separator for a secondary battery, for example, a separator for a lithium secondary battery.

[0064] An example of a method for producing a separation membrane may include the steps of: (a) dissolving or dispersing the copolymer composition in a solvent to prepare a polymer solution; (b) adding and mixing inorganic particles to the polymer solution of step (a); and (c) coating one or more regions selected from the group consisting of a surface of a polyolefin-based separation membrane substrate and a portion of pores in the substrate with the mixture of step (b) and drying.

[0065] First, 1) the copolymer composition is prepared in the form of a polymer solution by dissolving or dispersing it in a suitable solvent.

[0066] The solvent preferably has a solubility index similar to that of the copolymer composition used in the binder and a low boiling point. This is to facilitate uniform mixing and subsequent solvent removal. Non-limiting examples of usable solvents include acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water, or a mixture thereof. More preferably, the solvent is dispersed in water.

[0067] 2) Inorganic particles are added to and dispersed in the prepared polymer solution to prepare an inorganic particle and polymer mixture.

[0068] It is preferable to carry out a dispersion process of the polymer solution and the inorganic particles. In this case, the dispersion time is preferably 10 minutes to 5 hours. As the dispersion method, a conventional method can be used, and the ball mill method is particularly preferable.

[0069] The composition of the mixture consisting of inorganic particles and polymers is not greatly limited, and the thickness, pore size, and porosity of the finally manufactured organic / inorganic composite porous separator of the present invention can be controlled according to the composition.

[0070] That is, as the ratio of inorganic particles (I) to polymer (P) (ratio=I / P) increases, the porosity of the separator increases, which results in an increase in the thickness of the separator with the same solid powder content (weight of inorganic particles + weight of polymer). In addition, the possibility of pore formation between inorganic particles increases, and the pore size increases. At this time, as the size (particle size) of the inorganic particles increases, the interstitial distance between the inorganic particles increases, which increases the pore size.

[0071] 3) The mixture of inorganic particles and polymer thus produced is coated on a polyolefin-based separation membrane substrate, and then dried to obtain the separation membrane of the present invention.

[0072] In this case, the method of coating the mixture of inorganic particles and polymer on the polyolefin-based separation membrane substrate may be a conventional coating method known in the art, and may be various methods such as dip coating, die coating, roll coating, comma coating, or a combination thereof. In addition, when the mixture of inorganic particles and polymer is coated on the polyolefin-based separation membrane substrate, coating may be performed on both sides of the separation membrane substrate, or selectively on only one side of the separation membrane substrate.

[0073] When the separator is used in a secondary battery, lithium ions can be transferred not only through the separator substrate but also through the porous active layer, and the above-mentioned safety improvement effect can be achieved in the event of an internal short circuit caused by an external impact.

[0074] The secondary battery may include a positive electrode, a negative electrode, and the separator and electrolyte interposed between the positive electrode and the negative electrode.

[0075] The secondary battery may be manufactured by a conventional method known in the art. In one embodiment, the secondary battery is manufactured by assembling the electrodes and a separator therebetween, and then injecting an electrolyte into the assembly.

[0076] The electrode to be used with the separator is not particularly limited, and the positive electrode active material may be a common positive electrode active material used in a positive electrode of a secondary battery, non-limiting examples of which include lithium intercalation materials such as lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, or a composite oxide formed by a combination of these. The negative electrode active material may be a common negative electrode active material used in a negative electrode of a conventional electrochemical device, non-limiting examples of which include lithium metal or lithium alloy and lithium intercalation materials such as carbon, petroleum coke, activated carbon, graphite, or other carbons. The positive and negative electrode active materials are respectively attached to a positive current collector, i.e., a foil made of aluminum, nickel, or a combination thereof, and a negative current collector, i.e., a foil made of copper, gold, nickel, copper alloy, or a combination thereof, to form a positive electrode and a negative electrode.

[0077] The electrolyte is a salt having a structure of A+B-, where A+ includes an alkali metal cation such as Li+, Na+, or K+, or an ion consisting of a combination thereof, and B- includes an anion such as PF6-, BF4-, Cl-, Br-, I-, ClO4-, AsF6-, CH3CO2-, CF3SO3-, N(CF3SO2)2-, or C(CF2SO2)3-, or an ion consisting of a combination thereof. The electrolyte is a salt having a structure of A+B-, where A+ includes an alkali metal cation such as Li+, Na+, or K+, or an ion consisting of a combination thereof, and the salt includes an anion such as PF6-, BF4-, Cl-, Br-, I-, ClO4-, AsF6-, CH3CO2-, CF3SO3-, N(CF3SO2)2-, or C(CF2SO2)3-, or an ion consisting of a combination thereof. Preferably, the amine is dissolved and dissociated in an organic solvent such as dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (GBL), or a mixture thereof.

[0078] In applying the separator to a battery, in addition to the general winding process, lamination and folding processes of the separator and electrodes are possible.

[0079] The present application will be described in more detail below using examples, but the present application is not limited thereto.

[0080] [Production Example 1] Production of copolymer A reaction vessel was charged with 650 parts by weight of distilled water, 100 parts by weight of a monomer mixture, and N,N'-methylenebisacrylamide (MBA) as a first crosslinking agent, and the mixture was heated to 60°C and stirred while injecting high-purity nitrogen gas. A copolymer was produced by adding 0.1 to 0.5 parts by weight of potassium persulfate, a decomposition initiator, and the monomer mixture to 100 parts by weight of the monomer mixture in a reaction vessel prepared at 60°C to carry out a continuous polymerization reaction.

[0081] [Example 1] A copolymer was produced according to Production Example 1 using 70 parts by weight of acrylamide (AM) and 30 parts by weight of N-vinylpyrrolidone (VP) as a monomer mixture and 0.3 parts by weight of N,N'-methylenebisacrylamide as a first crosslinking agent.

[0082] Then, 0.1 parts by weight of diethanolamine (DEA) as a second crosslinking agent was added and reacted to prepare a copolymer for binder.

[0083] [Example 2] A binder copolymer was produced in the same manner as in Example 1, except that 50 parts by weight of acrylamide and 50 parts by weight of vinylpyrrolidone were used as the monomer mixture.

[0084] [Example 3] A binder copolymer was prepared in the same manner as in Example 1, except that 70 parts by weight of acrylamide, 20 parts by weight of vinylpyrrolidone, and 10 parts by weight of acrylic acid (AA) were used as the monomer mixture.

[0085] [Example 4] A binder copolymer was prepared in the same manner as in Example 1, except that 70 parts by weight of acrylamide, 20 parts by weight of vinylpyrrolidone, and 10 parts by weight of acrylonitrile (AN) were used as the monomer mixture.

[0086] [Example 5] A binder copolymer was produced in the same manner as in Example 1, except that 40 parts by weight of acrylic acid, 20 parts by weight of vinylpyrrolidone, and 40 parts by weight of acrylonitrile were used as the monomer mixture.

[0087] [Example 6] A binder copolymer was produced in the same manner as in Example 1, except that 70 parts by weight of acrylic acid and 30 parts by weight of vinylpyrrolidone were used as the monomer mixture.

[0088] [Comparative Example 1] A polymer was prepared according to Preparation Example 1 using only 100 parts by weight of acrylamide, not a monomer mixture, without using N,N'-methylenebisacrylamide as the first crosslinking agent, and used as a binder copolymer.

[0089] That is, a homopolymer of a non-crosslinked acrylamide polymer was used as the binder polymer.

[0090] [Comparative Example 2] A binder polymer was prepared in the same manner as in Comparative Example 1, except that 0.1 parts by weight of diethanolamine, which was a second crosslinking agent, was added and reacted later.

[0091] That is, a homopolymer of an acrylamide polymer crosslinked only with the second crosslinking agent was used as the binder polymer.

[0092] [Comparative Example 3] A binder polymer was prepared in the same manner as in Comparative Example 1, except that 0.3 parts by weight of N,N'-methylenebisacrylamide was used as the first crosslinking agent.

[0093] That is, a homopolymer of an acrylamide polymer crosslinked only with the first crosslinking agent was used as the binder polymer.

[0094] [Comparative Example 4] A binder polymer was prepared in the same manner as in Comparative Example 1, except that 0.3 parts by weight of N,N'-methylenebisacrylamide was used as the first crosslinking agent, and 0.1 parts by weight of diethanolamine was added later as the second crosslinking agent.

[0095] That is, a homopolymer of an acrylamide polymer crosslinked with a first crosslinking agent and a second crosslinking agent was used as the binder polymer.

[0096] [Comparative Example 5] A binder copolymer was prepared in the same manner as in Example 1, except that the first crosslinking agent, N,N'-methylenebisacrylamide, was not used, and 0.1 parts by weight of the second crosslinking agent, diethanolamine, was not added post-reacted.

[0097] That is, a non-crosslinked acrylamide-vinylpyrrolidone copolymer was used as the binder copolymer.

[0098] [Comparative Example 6] A binder copolymer was prepared in the same manner as in Example 1, except that the first crosslinking agent, N,N'-methylenebisacrylamide, was not used.

[0099] That is, an acrylamide-vinylpyrrolidone copolymer crosslinked only with the second crosslinking agent was used as the binder copolymer.

[0100] [Comparative Example 7] A binder copolymer was prepared in the same manner as in Example 1, except that 0.1 parts by weight of diethanolamine, the second crosslinking agent, was not added post-reacted.

[0101] That is, an acrylamide-vinylpyrrolidone copolymer crosslinked only with the first crosslinking agent was used as the binder copolymer.

[0102] [Comparative Example 8] A copolymer was produced according to Production Example 1 using 50 parts by weight of acrylic acid and 50 parts by weight of acrylonitrile as a monomer mixture and 0.3 parts by weight of N,N'-methylenebisacrylamide as a first crosslinking agent.

[0103] Then, 0.1 parts by weight of diethanolamine (DEA) as a second crosslinking agent was added and reacted to prepare a copolymer for binder.

[0104] The weight parts of the monomer, the first crosslinking agent and the second crosslinking agent in Examples 1 to 6 and Comparative Examples 1 to 8 are shown in Table 1 below.

[0105] [Table 1]

[0106] [Production Example 2] Production of slurry for porous membrane coating Inorganic particles (alumina, average particle size 0.5 μm) and the binder (co)polymers prepared in Examples 1 to 6 and Comparative Examples 1 to 8 were mixed in a solid powder weight ratio of 96:4, and then distilled water was added and mixed in such a way that the solid powder concentration became 35%. The mixture was thoroughly dispersed using a ball mill or a mechanical stirrer to prepare a slurry.

[0107] [Production Example 3] Production of separation membrane An inorganic coating layer is formed by applying the slurry for porous membrane coating prepared according to Preparation Example 2 to a polyolefin porous substrate (polyethylene (PE), polypropylene (PP), etc.). Various methods such as dip coating, die coating, gravure coating, and comma coating can be used as the coating method.

[0108] After coating, the coating was dried using warm air, hot air, vacuum drying, infrared drying, or the like, and the drying temperature range was 50 to 85°C.

[0109] The thickness of the inorganic coating layer is 0.5 to 6 μm on the cross section or both sides. If the thickness is less than 0.5 μm, the heat resistance of the separator is significantly reduced. If the thickness exceeds 6 μm, the separator is too thick, which reduces the energy density of the battery and increases the resistance.

[0110] [Evaluation Example 1] Adhesion strength of slurry for porous membrane coating A tape having a width of 18 mm and a length of 30 mm or more was attached onto the separator prepared according to Preparation Example 3 using the binder (co)polymers of Examples 1 to 6 and Comparative Examples 1 to 8, and then rolled five times with a hand roller to prepare a test specimen.

[0111] The prepared specimen was attached to a UTM (1kgf Load cell), one side of the separator was attached to the upper clip of the tensile strength tester, and the tape attached to the separator was attached to the lower clip, and the 180° peel strength was measured at a speed of 100mm / min. Five or more specimens were prepared per sample and measured, and the average value was calculated.

[0112] [Evaluation Example 2] Heat shrinkage rate of separation membrane (dry heat resistance) The separator prepared according to Preparation Example 3 using the binder (co)polymers of Examples 1 to 6 and Comparative Examples 1 to 8 was prepared as a sample having a length and width of 5 x 5 cm. The sample was left in an oven at 150°C for 1 hour, and then the shrinkage rate was measured.

[0113] [Evaluation Example 3] Heat shrinkage rate of separator after electrolyte immersion (wet heat resistance) The separators prepared according to Preparation Example 3 using the binder (co)polymers of Examples 1 to 6 and Comparative Examples 1 to 8 were prepared as samples measuring 5 x 5 cm in length and width, and the samples were placed in pouches with electrolyte and sealed, and then immersed for about 12 hours. Thereafter, a gas outlet was made in the pouch, and the pouches were left in an oven at 150°C for 1 hour, after which the samples were taken out and the shrinkage was measured.

[0114] The evaluation results of Evaluation Examples 1 to 3 are shown in Table 2 below.

[0115] [Table 2]

[0116] As shown in Table 2, the separators prepared using the binder copolymers of Examples 1 to 6 exhibited lower heat shrinkage rates (especially heat shrinkage rates after impregnation with an electrolyte) than the separators prepared using the binder (co)polymers of Comparative Examples 1 to 8, and were therefore confirmed to have excellent heat resistance.

[0117] Specifically, the separators prepared using the binder copolymers of Examples 1 to 6 exhibit lower heat shrinkage rates (especially the heat shrinkage rate after impregnation with an electrolyte) than the separators prepared using the binder polymers of Comparative Examples 1 to 4, which use a single acrylamide polymer.

[0118] In particular, in comparison with the separator using the binder polymer of Comparative Example 4, which was crosslinked using the first and second crosslinking agents in the same manner as the binder copolymers of Examples 1 to 6, when vinylpyrrolidone was used as the monomer, the adhesive strength was slightly reduced, but the heat shrinkage rate of the separator (especially the heat shrinkage rate after impregnation with an electrolyte) was significantly reduced, thereby demonstrating excellent heat resistance.

[0119] Meanwhile, when comparing the separator prepared using the binder copolymer of Example 1 with the separator prepared using the binder copolymers of Comparative Examples 5 to 7, the separator prepared using the binder copolymer of Comparative Example 5 had vinylpyrrolidone dissolved in the electrolyte, and therefore the thermal shrinkage rate of the separator after immersion in the electrolyte could not be measured.

[0120] That is, the heat resistance of the separator produced using the binder copolymer of Comparative Example 5 without using the first crosslinking agent and the second crosslinking agent after impregnation with the electrolyte solution was significantly reduced. Similarly, the heat resistance of the separator prepared using the binder copolymer of Comparative Example 6, which did not use the first crosslinking agent, after impregnation with the electrolyte solution was significantly reduced compared to the separator prepared using the binder copolymer of Example 1.

[0121] In addition, the separation membrane produced using the binder copolymer of Comparative Example 7, which did not use a second crosslinking agent, had an increased thermal shrinkage rate and decreased heat resistance compared to the separation membrane produced using the binder copolymer of Example 1.

[0122] In particular, the separator prepared using the binder copolymer of Comparative Example 7 had improved heat resistance after impregnation with an electrolyte compared to the separator prepared using the binder copolymers of Comparative Examples 5 and 6, but the heat resistance of the separator after impregnation with an electrolyte was still lower than that of the separator prepared using the binder copolymer of Example 1.

[0123] That is, the first crosslinking agent contributes to improving the heat resistance after impregnation with the electrolyte, but the heat resistance after impregnation with the electrolyte is decreased compared to the case where both the first crosslinking agent and the second crosslinking agent are used.

[0124] Meanwhile, the first and second crosslinking agents were used as in Examples 1 to 6, but the separator prepared using the binder copolymer of Comparative Example 8 in which only acrylamide monomer and acrylonitrile monomer were polymerized had significantly lower heat resistance, especially after impregnation with an electrolyte, than the separator prepared using the binder copolymer of Examples 1 to 6.

[0125] As a result, the separator prepared using the binder copolymer of the embodiment in which the first crosslinker and the second crosslinker were used had excellent substrate adhesion and excellent heat resistance at 150° C. In particular, the excellent heat resistance at 150° C. was maintained even after being impregnated with an electrolyte.

[0126] The scope of the present invention is indicated by the claims set forth below rather than by the above detailed description, and all modifications and variations that come within the meaning and scope of the claims, as well as their equivalent concepts, should be interpreted as being included within the scope of the present invention. [Industrial Applicability]

[0127] The copolymer composition of the present invention can improve the adhesive strength and heat resistance of the slurry composition, increase the adhesive strength with the polyolefin film that is the separation membrane substrate, and improve the heat resistance of the separation membrane (particularly, the heat resistance when impregnated with an electrolyte).

[0128] In addition, a battery having excellent life characteristics and safety can be realized.

Claims

1. a copolymer including at least one monomer unit selected from the group consisting of acrylate-based monomer units, acrylonitrile-based monomer units, vinylamide-based monomer units, and acrylamide-based monomer units in an amount of 30% by weight or more and 80% by weight or less, based on 100% by weight of the total copolymer weight, and at least 20% by weight or more and 70% by weight or less of vinylpyrrolidone monomer units; and a crosslinking agent; Including, Copolymer composition.

2. The acrylate monomer unit is formed by polymerizing acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, glycidyl acrylate, glycidyl methacrylate, or a combination thereof; The acrylonitrile-based monomer unit is formed by polymerizing acrylonitrile, methacrylonitrile, or a combination thereof; The vinylamide monomer unit is formed by polymerizing vinyl acetamide, methyl vinyl acetamide, vinyl formamide, or a combination thereof; The acrylamide monomer unit is formed by polymerizing acrylamide, methacrylamide, N-methylmethacrylamide, hydroxyethyl acrylamide, hydroxyethyl methacrylamide, dimethylacrylamide, or a combination thereof; The vinylpyrrolidone monomer unit is formed by polymerizing vinylpyrrolidone. The copolymer composition of claim 1.

3. The copolymer includes a monomer repeat structure represented by the following formula 1: The copolymer composition of claim 1. 【Chemistry 1】 In Equation 1, R 1 Or R 5 are each independently hydrogen or a linear or branched hydrocarbon having 1 to 4 carbon atoms; X 1 and X 2 are each independently hydrogen or a linear or branched hydrocarbon having 1 to 20 carbon atoms; X 3 is hydrogen, a linear or branched hydrocarbon or acid having 1 to 20 carbon atoms, X 4 is a linear or branched hydrocarbon or alcohol having 1 to 20 carbon atoms; a, b, c, d, e, and f satisfy a+b+c+d+e+f=1; a is 0.2 to 0.7, and b+c+d+e+f is 0.3 to 0.8, b, c, d, e and f are each from 0 to 0.

8. (However, one or more of b, c, d, e, and f is not 0.)

4. The crosslinking agent includes at least one selected from the group consisting of a first crosslinking agent and a second crosslinking agent; the first crosslinker comprises a double bond; The second crosslinker is a compound represented by the following formula 2: The copolymer composition of claim 1. 【Chemistry 2】 In the above Chemical Formula 2, R 6 Or R 8 are each independently hydrogen, a linear or branched hydrocarbon having 1 to 6 carbon atoms, an alcohol having 1 to 6 carbon atoms, an acid having 1 to 6 carbon atoms, or a combination thereof; Copolymer composition.

5. The first crosslinking agent may be polyethylene glycol diacrylate, N,N'-methylenebisacrylamide, divinyl adipate, butanediol divinyl ether, cyclohexanedimethane divinyl ether, 1,6-divinylperfluorohexane, or perfluorohexanediol diacrylate.

5. The copolymer composition of claim 4, wherein the copolymer composition is a copolymer of the formula (I) and the formula (II).

6. The content of the first crosslinking agent is 0.05 parts by weight or more and 5 parts by weight or less, and the content of the second crosslinking agent is 0.05 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the copolymer. The copolymer composition of claim 4.

7. The copolymer composition according to any one of claims 1 to 6, and inorganic particles, Slurry Composition.

8. The slurry composition of claim 7, Separation membrane.

9. The separation membrane according to claim 8, Secondary battery.

Citation Information

Patent Citations

  • Ionic soft contact lens

    JP1994289335A

  • PVA-based contact lens

    JP1994347729A

  • Coating composition for non-aqueous electrolyte secondary battery

    JP2008287888A

  • Binder for secondary battery porous films, slurry composition for secondary battery porous films, porous film for secondary batteries, and secondary battery

    JP2015185530A

  • CERAMIC BINDER COMPOSITION FOR CERAMIC-COATED SEPARATOR FOR LITHIUM-ION BATTERY, PRODUCTION METHOD AND USE THEREOF

    JP2018509493A